Analysis of dominant factors in enhancing muslim tourist satisfaction at halal tourism destinations - Purnomo, Singgih; Purwandari, Suci (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
This research examines the influence of halal tourism potential on Muslim tourist satisfaction at Torohudan Beach and Ngrenean Beach in Kanigoro Village. The study aims to identify the most dominant factors influencing tourist satisfaction, explicitly focusing on halal tourism destinations, accommodations, and travel services. A quantitative approach was employed, with data collected from 96 respondents using questionnaires. The data were analyzed using partial tests (t-tests) and Importance-Performance Analysis (IPA) to assess each variable's significance and prioritize improvement areas. The results indicate that all three components—halal destinations, accommodations, and travel agencies—significantly impact tourist satisfaction. Among these, halal accommodations emerged as the most dominant factor, highlighting the importance of providing halal-compliant facilities, such as halal-certified food and prayer spaces. The IPA identified halal tourism destinations and the availability of halal-certified dining options as key areas for improvement, as they were rated highly in importance but exhibited lower performance. The study suggests that improving these areas can substantially increase tourist satisfaction and enhance the competitiveness of these destinations. The findings have implications for local tourism managers, indicating where to focus efforts and resources to better cater to the needs of Muslim tourists and boost overall visitor satisfaction